2015
DOI: 10.5603/fhc.a2015.0022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal age on the expression of mesenchymal stem cell markers in the components of human umbilical cord

Abstract: Introduction. Although the human umbilical cord (UC) has been previously considered a medical waste, its use as a main source of fetal stem cells for regenerative medicine applications has increased over the past few years. The aim of the study was to assess the impact of the maternal age on the expression of mesenchymal stem cells (MSC) markers CD105 and CD29 in the different areas of human UC. Material and methods. In this comparative cross sectional study, one hundred term UCs from five maternal age groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…This trend has been confirmed in other skin stem cells, such as hair follicle stem cells (Giangreco et al 2008 ; Keyes et al 2013 ; Schultz and Sinclair 2016 ). Although some researchers detected decreased expression of mesenchymal stem cell markers in components of the human umbilical cord, as well as a trend for age-related changes of stem cell markers, we were unable to find many studies that illustrate the change of stem cell numbers with age (Alrefaei et al 2015 ; Cuevas-Diaz Duran et al 2013 ). Instead, regarding skin stem cells, some studies have found that the number of stem cells increases or does not vary with age (Keyes et al 2013 ; Schultz and Sinclair 2016 ).…”
Section: Discussionmentioning
confidence: 80%
“…This trend has been confirmed in other skin stem cells, such as hair follicle stem cells (Giangreco et al 2008 ; Keyes et al 2013 ; Schultz and Sinclair 2016 ). Although some researchers detected decreased expression of mesenchymal stem cell markers in components of the human umbilical cord, as well as a trend for age-related changes of stem cell markers, we were unable to find many studies that illustrate the change of stem cell numbers with age (Alrefaei et al 2015 ; Cuevas-Diaz Duran et al 2013 ). Instead, regarding skin stem cells, some studies have found that the number of stem cells increases or does not vary with age (Keyes et al 2013 ; Schultz and Sinclair 2016 ).…”
Section: Discussionmentioning
confidence: 80%
“…It has been demonstrated that MSCs age in different organs [34], and that the increase in reactive oxygen species and epigenetic changes may underlie these alterations [31,35,36], that may well be at work also in aged placentas. Interestingly, Alrefaei et al [37] determined by an immunohistochemistry study on MSCs in AM and Warthon's jelly of the umbilical cord, that CD105 and CD29 expression showed an inverse correlation with age, with the least expression in women aged older than 40 years. As concerning pre-eclampsia, this pathological condition is thought to be due to inadequate placental cytotrophoblast invasion, followed by widespread maternal endothelial dysfunction, which leads to placental hypoperfusion and ischemia [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that WJ-MSCs derived from the extreme cord segments are better source of MSCs compared with cells from the middle segment because of their higher proliferation rate and viability [28]. In the research on 100 term pregnancies, from five maternal age groups (20-45 years), reduced number of cells as well as the level of MSCs markers expression were reported in older mothers [29].…”
Section: Discussionmentioning
confidence: 99%